2008
DOI: 10.1152/ajpendo.90367.2008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adlay hull extracts on uterine contraction and Ca2+mobilization in the rat

Abstract: hull extracts on uterine contraction and Ca 2ϩ mobilization in the rat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 46 publications
3
20
2
Order By: Relevance
“…Reports of uterine relaxant effects include Hsia et al. () who demonstrated that fractionated phytosterols extracted from Adlay ( Coix lachryma‐jobi L. var. ma‐yuen Stapf .)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports of uterine relaxant effects include Hsia et al. () who demonstrated that fractionated phytosterols extracted from Adlay ( Coix lachryma‐jobi L. var. ma‐yuen Stapf .)…”
Section: Discussionmentioning
confidence: 99%
“…Phytosterols and saponins can act as inhibitors of the SR CaATPase and potassium channels, and in this way can increase the contractile activity (Bao et al 2006;Promprom et al 2010;Kupittayanant et al 2014). Reports of uterine relaxant effects include Hsia et al (2008) who demonstrated that fractionated phytosterols extracted from Adlay (Coix lachryma-jobi L. var. ma-yuen Stapf.)…”
Section: Discussionmentioning
confidence: 99%
“…8 Some experiments have shown that glycosylation limits the antioxidant activity of flavonoids in vitro. 9 Among the various types of flavonoids, naringenin (4 ,5,7-trihydroxyflavanone), found especially in many citrus fruits, has been shown to possess antioxidant, anti-inflammatory, antiproliferative and antimutagenic properties, 3,10 and recent studies suggest that it could be a useful chemoprotective agent. 11 Naringin (4 ,5,7-trihydroxyflavanone 7-rhamnoglucoside), a glycoside of naringenin, is a main cause of bitterness in some citrus juices, it is rapidly transformed into naringenin by the action of enzymes such as α-rhamnosidase and β-glucosidase.…”
Section: Introductionmentioning
confidence: 99%
“…Both these substances inhibit the signal transduction pathway of the androgen receptor, inhibiting androgen activity (Tsai et al, 2009). Additionally, naringenin and apigenin were isolated from AH and AB extracts, and luteolin was identified in adlay extracts (Chen, Lo, & Chiang, 2012;Hsia, Kuo, Chiang, & Wang, 2008;Kuo et al, 2002). These results indicated that adlay extracts also contain components that could inhibit signal transduction pathways of the androgen receptor.…”
Section: Discussionmentioning
confidence: 94%